Penilaian Ekonomi Wisata Pesisir Kawasan Carocok Painan, Kabupaten Pesisir Selatan, Sumatera Barat - Khairunnisa, Khairunnisa; Kusumastanto, Tridoyo; Fahrudin, Achmad (UI Scholars Hub, 2017)
Carocok Painan is one of the potential areas for coastal tourism in Pesisir Selatan Regency. The area has beautiful beaches, coastal resources and historical sites that attract tourists. This study aims to estimate the supply and demand for coastal tourism in Carocok Painan. The supply conditions based on water quality analysis, suitability area, and carrying capacity show that the Carocok Painan is suitable for coastal tourism. The analysis of demand shows that the economic value of Carocok Painan for tourists using the travel cost method is Rp41,521,536,000 per year, while the economic value for residents using contingent valuation method is Rp347,756,632 per year.